Existence and uniqueness of solutions of higher-order antiperiodic dynamic equations. Issue 4 (14th December 2004) - Cabada, Alberto; Vivero, Dolores R.
Abstract : We prove existence and uniqueness results in the presence of coupled lower and upper solutions for the generaln th problem in time scales with linear dependence on thei thΔ -derivatives fori = 1, 2, …, n, together with antiperiodic boundary value conditions. Here the nonlinear right-hand side of the equation is defined by a functionf ( t, x ) which isrd -continuous int and continuous inx uniformly int . To do that, we obtain the expression of the Green's function of a related linear operator in the space of the antiperiodic functions.